2019
DOI: 10.3389/fphar.2019.00649
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Curcumin on Weight Loss Among Patients With Metabolic Syndrome and Related Disorders: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Background and objective: The current systematic review and meta-analysis of randomized controlled trials (RCTs) was carried out to assess the influence of curcumin intake on weight among patients with metabolic syndrome and related disorders. Methods: We searched the following databases up until January 2018: MEDLINE, EMBASE, Web of Science, and Cochrane Central Register of Controlled Trials. The relevant data were extracted and evaluated for quality of the studies in accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 41 publications
0
56
0
2
Order By: Relevance
“…In obese women with polycystic ovary syndrome (PCOS), 1000 mg/day curcumin supplementation (500 mg twice daily: 70–80% curcumin, 15–20% demethoxycurcumin and 2.5–6.5% bisdemethoxycurcumin) for six weeks improved serum insulin and the Quantitative Insulin Sensitivity Check Index [ 45 ]. A recent meta-analysis reported that curcumin intake was associated with reduced body mass index (BMI), body weight, body fat, leptin value, and increased adiponectin levels in patients with metabolic syndrome and related disorders [ 46 ]. Overall, the dosage and duration of curcumin supplementation appear to differently modulate glucose metabolism in humans.…”
Section: Role Of Curcumin In Pregnancymentioning
confidence: 99%
“…In obese women with polycystic ovary syndrome (PCOS), 1000 mg/day curcumin supplementation (500 mg twice daily: 70–80% curcumin, 15–20% demethoxycurcumin and 2.5–6.5% bisdemethoxycurcumin) for six weeks improved serum insulin and the Quantitative Insulin Sensitivity Check Index [ 45 ]. A recent meta-analysis reported that curcumin intake was associated with reduced body mass index (BMI), body weight, body fat, leptin value, and increased adiponectin levels in patients with metabolic syndrome and related disorders [ 46 ]. Overall, the dosage and duration of curcumin supplementation appear to differently modulate glucose metabolism in humans.…”
Section: Role Of Curcumin In Pregnancymentioning
confidence: 99%
“…In addition, a significant reduction of BMI and liver fat was also observed by Rahmani et al after the administration of 70 mg/day curcumin for eight weeks among people with NAFLD [179]. Another more recent line of evidence is represented by a systematic review and metanalysis of 21 RCTs which indicated that curcumin intake significantly reduced BMI, weight, and waist-circumference [180]. However, not all reports point in the same promising direction.…”
Section: Curcuminmentioning
confidence: 79%
“…The anti-obesity effects of curcumin and curcuminoids are being investigated extensively in clinical and animal model-based studies [ 12 , 34 , 35 ]. In clinical obesity studies, curcumin intake improved a set of pivotal body composition parameters, including reducing body weight, body mass index (BMI), and waist circumference and modulating the adiponectin and leptin levels [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The anti-obesity effects of curcumin and curcuminoids are being investigated extensively in clinical and animal model-based studies [ 12 , 34 , 35 ]. In clinical obesity studies, curcumin intake improved a set of pivotal body composition parameters, including reducing body weight, body mass index (BMI), and waist circumference and modulating the adiponectin and leptin levels [ 34 ]. Based on the body surface area normalization method of animal-to-human drug dose conversion [ 36 ], and daily food consumption rate for mice observed in our previous studies, 0.7% w / w curcumin corresponds to 5 g/day curcumin consumption by a 75-kg adult human.…”
Section: Discussionmentioning
confidence: 99%